2020
DOI: 10.3390/ijms21061921
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome-Based Mining and Expression Profiling of Transcription Factors Related to Cold Tolerance in Peanut

Abstract: Plants tolerate cold stress by regulating gene networks controlling cellular and physiological traits to modify growth and development. Transcription factor (TF)-directed regulation of transcription within these gene networks is key to eliciting appropriate responses. Identifying TFs related to cold tolerance contributes to cold-tolerant crop breeding. In this study, a comparative transcriptome analysis was carried out to investigate global gene expression of entire TFs in two peanut varieties with different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 68 publications
(74 reference statements)
3
21
0
Order By: Relevance
“…In this study, 147 TFs belonging to 32 TF families, including AP2/ERF (27), MYB (19), bHLH (13), WRKY (21), C 2 H 2 (8), and NAC (13), were largely regulated by cold stress (Table 2, Figure 5). Similar to our findings, in previous studies, comparative transcriptome analysis of rice, Chinese jujube, and peanut under cold stress conditions identified the above TF families to be the most regulated gene members [60,61,71,72]. These TF genes in their respective families are divided into diverse subgroups based on their specific motif structures, showing that they may perform their specific biological activities under cold stress.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, 147 TFs belonging to 32 TF families, including AP2/ERF (27), MYB (19), bHLH (13), WRKY (21), C 2 H 2 (8), and NAC (13), were largely regulated by cold stress (Table 2, Figure 5). Similar to our findings, in previous studies, comparative transcriptome analysis of rice, Chinese jujube, and peanut under cold stress conditions identified the above TF families to be the most regulated gene members [60,61,71,72]. These TF genes in their respective families are divided into diverse subgroups based on their specific motif structures, showing that they may perform their specific biological activities under cold stress.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, the expression of WRKY70 and TcWRKY53 was induced by cold stress in wheat and Thlaspi caerulescens, respectively [75,76]. Moreover, peanut cold stress tolerance was regulated by WRKY70 and WRKY53 via the plant-pathogen interaction pathway [72]. Moreover, MYB4 (Zm00001d041853), bHLH57 (Zm00001d027419), PIF4 (Zm00001d013130), PTF1 (Zm00001d045046), AGL22 (Zm00001d018142), GRF6 (Zm00001d000238), ATHB4 (Zm00001d002754), Scl7 (Zm00001d033834), BTB/POZ (Zm0000 1d023313, Zm00001d030864), and C 2 H 2 (Zm00001d024883) were all enhanced in the tolerant lines in this study (Tables S5 and S6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to the CBF transcription factor family, such TFs as MYB, NAC, bZIP, and WRKY also play important roles in plant cold resistance [49][50][51][52][53][54][55][56][57][58][59][60][61]. The expression of WRKY TFs is induced by external environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…At present, comparative transcriptomics has been widely used to illustrate the complex genes regulatory networks of many plants under cold stress. Comparative transcriptome analysis in two peanut varieties with different cold-tolerant abilities showed that 445 TF genes were significantly differentially expressed under cold and revealed some possible mechanism in peanut cold tolerance [17]. The comparison transcriptome of the tea plant under cold found that 978 differentially expressed genes (DEGs) owned by the tolerant and sensitive plants were enriched in pathways of photosynthesis and hormone signal transduction, among others, and considered that the different expression of Lhca2 and SNF1-related protein kinase 2 (SnRK2) are correlated with cold tolerance [18].…”
Section: Introductionmentioning
confidence: 99%